943. DENDROBIUM HESPERIS: Orchidaceae. (13th August 2020) - Kumar, Pankaj; Sharma, Jyotsna; Isaac‐Williams, Mark; Rawat, Gopal Singh
Summary: Dendrobium hesperis (Seidenf.) Schuit. & P.B.Adams (Orchidaceae: Epidendroideae: Dendrobieae), an interesting but lesser‐known orchid, referred to in earlier literature as Flickingeria hesperis Seidenf., was formerly believed to be endemic to the Gori Valley (Uttarakhand), the westernmost orchid hotspot in the Indian Himalayas. Originally described from western Himalayas in 1982, this species was later discovered in Manipur in northeast India in 2014, thereafter reported from Laos in 2020. This note is intended to provide correct nomenclature and updated distribution of this taxon along with diagnostic features and illustration to aid its identification.